Suitability of a classic wastewater treatment plant to purify the collective effluent of Oum El-Bouaghi City, North East Algeria - Dounia Dib; Miyada Ouanes; Mamoun Fellah; Bachir Khezzani; Dalila Addad; Kenza Kadi; Mounia Ouldjaoui; Abdelkader Khiari; Alejandro Perez-Larios; Benjamin Castañeda-Pimienta; Mariano Aceves-Aldrete; Souren Gregorian; et al. (Applied Water Science)
Abstract Due to water shortages in semi-arid regions of Algeria, reusing treated waste water for irrigation is necessary. This study aims to demonstrate how the biological treatment methods used in Algerian plants can be applied to the domestic sewage of Oum El-Bouaghi City, located in northeastern Algeria. Twenty-one parameters were monitored to evaluate the effectiveness of the treatment techniques. Over 2 weeks, the samples were continuously collected via an automated sampler (Hach Lange type). We have determined the most critical parameters in wastewater: pH, EC, T, O2, ORP, BOD5, COD, MES, MVS, N–NTK, NO3 −, NO2 −, NH4 +, P.T., oils and fats, and metallic elements: Zn, Pb, Cd, Cr, Cu, and Ni. The findings indicate that biological treatment methods effectively purify the effluent of Oum El-Bouaghi City. The BOD5/COD ranges between 0.47 and 0.55, demonstrating that biological processes can efficiently break down the pollutant load. The inverse ratio (COD/BOD5) inferior to 3 (1.77 to 2.25) indicates their domestic origin. The results of the PCA projection on the F1*F2 plan show a robust positive correlation between BOD5 and several organic pollution indicators, as follows: r = 0.94 with COD, MES, and NH4 +, r = 0.96 for both NO3 − and NO2 −. r = 0.89 for total phosphorus. Similar strong correlations were observed with COD, reflecting the ease of organic compound oxidation via chemical processes. Over-studied heavy metals, chromium stands out as the sole element demonstrating substantial connections with other elements with correlation coefficients of 0.63 to 0.82, showing its reactivity and unstable behavior. These findings emphasize the efficiency of the biological treatment procedures in purifying the effluent of Oum El-Bouaghi city regarding their domestic character.